1999
DOI: 10.1002/(sici)1099-1581(199901/02)10:1/2<78::aid-pat771>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Performance in paper coating of styrene/acrylate copolymer latex

Abstract: Copolymer latexes of styrene and acrylates (mainly butyl acrylate) were synthesized. Sodium dodecyl sulfate and ethoxylated nonyl phenol containing ten ethylene oxide units were used as surfactants, and potassium persulfate was used as initiator. Coating for paper was made based on the copolymer latexes with white pigments. The performances of coated paper were measured. By varying experimental conditions such as comonomer proportion and amounts of emulsifiers and of initiator, a copolymeric latex suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The behavior of the curve may be described as follows: according to the above results and the literature, 11 silicone-modified ST-BA copolymer forms an IPN parallel to the directional arrangement of side-chain methyl in silicones, and the silicone segments within copolymers tend to migrate to the air-polymer interface. Therefore, the reflection of light by the copolymer film tends to be more regular, because of the formation of a uniform coating, 3 and the corresponding coated paper will exhibit higher glossiness. However, it is reasonable to assume that D 4 may partially be polymerized to silicones by accumulating near the film-air interfaces, and it is found that a part of the silicone floats on the emulsion surface in the synthesis experiment if excess D 4 is added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of the curve may be described as follows: according to the above results and the literature, 11 silicone-modified ST-BA copolymer forms an IPN parallel to the directional arrangement of side-chain methyl in silicones, and the silicone segments within copolymers tend to migrate to the air-polymer interface. Therefore, the reflection of light by the copolymer film tends to be more regular, because of the formation of a uniform coating, 3 and the corresponding coated paper will exhibit higher glossiness. However, it is reasonable to assume that D 4 may partially be polymerized to silicones by accumulating near the film-air interfaces, and it is found that a part of the silicone floats on the emulsion surface in the synthesis experiment if excess D 4 is added.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 These latexes are able to improve the surface strength, the glossiness, the water resistance, and the printing adaptability of the coated paper. 3 Recently, major breakthroughs in synthesis and applied performance of silicone-modified acrylate latex have been reported. 4 -6 The siliconemodified latex appears to possess the advantages of both silicone and acrylate resin in overcoming the high cost of silicone or the poor performance of acrylate resin in thermal stability and resisting water.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene/acrylic based copolymer particles can play an important role in a wide range of applications such as coatings [12], drug delivery [13] and biomedicine [14]. In addition, there is a great demand for the incorporation of fluorescent and magnetic properties into these particles due to its multidimensional properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Copolymers containing phthalimide derivatives have been used as optical brightening agents (2). Methacrylic copolymers with styrene have been widely used for the production of transparent film (3) and in paper coating (4). The composition of copolymers and the reactivity ratios of the comonomers have been determined by 1 H-NMR spectroscopic techniques (5)(6)(7)(8) for evaluating the specific application of copolymers.…”
Section: Introductionmentioning
confidence: 99%